2012
DOI: 10.1111/j.1365-2435.2012.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Don’t bite the hand that feeds: assessing ecological impacts of provisioning ecotourism on an apex marine predator

Abstract: Summary1. There has been considerable debate over the past decade with respect to wildlife provisioning, especially resultant behavioural changes that may impact the ecological function of an apex predator. The controversy is exemplified by the shark diving industry, where major criticisms based on inference, anecdote and opinion stem from concerns of potential behaviourally mediated ecosystem effects because of ecotourism provisioning (aka 'chumming' or feeding).2. There is a general lack of empirical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
150
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 62 publications
(102 reference statements)
16
150
1
Order By: Relevance
“…We found that tiger sharks spent more time at the surface during winter, potentially to enhance thermoregulation in warmer surface waters (Holland et al 1992). Moreover, during the winter, tiger shark core use areas were in the Bahamas, south of loggerhead turtle core use areas, probably such that tiger sharks could take advantage of warmer waters (Hammerschlag et al 2012a). Thus, the low turtle-shark overlap in winter could be a result of temperature primarily limiting their interactions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We found that tiger sharks spent more time at the surface during winter, potentially to enhance thermoregulation in warmer surface waters (Holland et al 1992). Moreover, during the winter, tiger shark core use areas were in the Bahamas, south of loggerhead turtle core use areas, probably such that tiger sharks could take advantage of warmer waters (Hammerschlag et al 2012a). Thus, the low turtle-shark overlap in winter could be a result of temperature primarily limiting their interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Such an approach has previously been used by Hammerschlag et al (2012b). Moreover, home ranges for turtles and sharks are consistent between years (Hawkes et al 2011, Hammerschlag et al 2012a.…”
Section: Satellite Trackingmentioning
confidence: 88%
See 2 more Smart Citations
“…Although we were unable to confirm that presence at the provisioning site each visit resulted in food consumption, it was clear from the number of sharks detected at this site's receiver, and those in close proximity, this activity was concentrating great hammerheads to the west of South Bimini. However, like tiger and white sharks that are regularly provisioned in Grand Bahama and Australia, respectively (Hammerschlag et al, 2012;Bruce and Bradford, 2013), great hammerheads continued to make longdistance migrations and departed at different times during the winter season.…”
Section: Site Fidelity and Residencymentioning
confidence: 99%